Revenue equalization and personal income tax in Estonian municipalities - Viktor Trasberg (European Regional Science Association (ERSA), 2010)
The main tax income for the sub-national governments in Estonia is personal income tax (PIT), which is shared between central and local governments. Since 2004, the share of that tax which is allocated to local governments has been steadily growing. Also, various grants from the central budget to local ones have increased. The situation changed radically during recession years. To cope with the central budget deficit, the central government cut transfers to the local governments and redistributed the PIT revenues in favor of central budget. As a result, the local governments' fiscal situation deteriorated significantly. Also, local governments' ability to attract additional funds from EU sources (e.g. structural funds) has been lessened. The research paper concentrates on the analyses of PIT income revenue fluctuations across the local governments and recession impact on various sub-national government groups. There is different importance (share) of PIT revenues in the local budgets. Then higher the incomes in a jurisdiction, there is also larger municipality's PIT revenue. Using econometric methods, there will be analyzed municipalities revenue factors, impact of central government policies and municipalities fiscal position in the situation of sharp economic fluctuations. Additionally will be generalized municipalities activities to cope with economic recession - the measures to support jurisdictions' residents in situation of declining public and individual revenues and other hand, increasing need for social services.
Keywords: 330